PEREMPUAN SAMIN PASCA-REFORMASI: PERSPEKTIF EKOFEMINISME : ECOFEMINIST PERSPECTIVES - Muhammad Khoiruddin; Tricahyono, Danan; Handayani, Rinda (Jurnal Masyarakat dan Budaya, 2023)
This paper departs from the lack of historical studies that discuss the issue of ecofeminism in Indonesia. The purpose of writing this article is to describe Samin women and nature in the concept of ecofeminism, the rejection of cement factories by Samin women, and the balance of the roles of women and men in the domestic sphere when Samin women resist. This study used a historical method consisting of four steps: 1. Heuristics is the collection of historical sources. 2. Verify sources. 3. Through external and internal criticism. 4. Interpretation of data that has been obtained through the process of data synthesis and analysis. 4. Historiography is writing history using descriptive analysis. The results of this study show that ecofeminism first developed in the West in the 1970s—1980s. Historically, the people’s movement began during the Dutch colonial government. The motives of the Samin community movement are based on social, economic, and spiritual factors. Samin women show the concept of Samin women with nature, and nature has a fairly respectable position. This is reflected in the view of the Samin people, who represent the earth as “mother”. This shows the close relationship between the earth and women. The driving factor for the transformation of Samin women from the domestic sphere to the public sphere is the green revolution of globalization. The post-reform Samin women’s movement is evidenced by her involvement in rejecting cement development in the Sukolilo area, Pati, Central Java.